Audiences as Publics. Tweeting with the Television on. - D'heer, Evelien; Verdegem, Pieter; Courtois, Cédric (AoIR Selected Papers of Internet Research, 2013)
Watching and talking about television is no longer a private experience confined to the living room. This paper presents a study on Twitter conversation whilst watching television and discusses the findings in the ongoing debates on Twitter research. Via a multi-method approach, we investigate Twitter conversation on a Belgian current affair program. Through the interpretation of the public character of meaning-making, we acknowledge how viewers come to constitute publics. In addition, specific ethical and theoretical issues related to the study are defined and discussed. Via the description of practical examples, we contribute to the ongoing discussion on internet research and Twitter research in particular. Future endeavors are outlined to grasp and understand audience activity in this media manifold.